The impact of combat sports on undergraduate students’ subjective well-being: chain mediation effects of emotional intelligence and self-esteem - Ying, Lei; Yang, Qingqing (Frontiers in Psychology, 2025)
BackgroundWith the continuous development of positive psychology, undergraduate students’ subjective well-being has increasingly become a focal point for researchers. Combat sports, as an effective means of promoting mental health, have significant potential for enhancing undergraduate students’ subjective well-being, yet the underlying mechanisms warrant in-depth investigation. This study aimed to explore the impact of combat sports on undergraduate students’ subjective well-being and examine the chain mediation effects of emotional intelligence and self-esteem.MethodsThis study employed a cross-sectional design to collect data from undergraduate students participating in combat sports across 10 universities in Sichuan Province, China, through questionnaire surveys. The research instruments included the Physical Activity Rating Scale, Subjective Well-being Scale, Emotional Intelligence Scale, and Self-esteem Scale to comprehensively assess participants’ psychological and behavioral characteristics. Following data collection, statistical analysis was conducted using SPSS 26.0, with structural equation modeling (AMOS) and Bootstrap methods employed to examine potential mediation effects and ensure reliability of the findings.ResultsThe analysis revealed significant positive correlations among combat sports participation, subjective well-being, emotional intelligence, and self-esteem. Specifically, combat sports demonstrated a significant direct effect on undergraduate students’ subjective well-being, indicating that participation in combat sports directly enhances individuals’ well-being levels. Furthermore, emotional intelligence and self-esteem exhibited chain mediation effects between combat sports and subjective well-being, whereby combat sports indirectly influenced subjective well-being by enhancing individuals’ emotional intelligence and self-esteem.ConclusionCombat sports not only directly predict undergraduate students’ subjective well-being but also indirectly influence subjective well-being through the psychological mediating variables of emotional intelligence and self-esteem. This study elucidates the underlying mechanisms linking combat sports participation and undergraduate students’ subjective well-being, providing empirical support and theoretical foundation for enhancing undergraduate students’ subjective well-being and maintaining their mental health through combat sports participation.